A COMPARATIVE IMPORT DEMAND FUNCTION FOR BRICS AND G7 - Damiyano D.; Mago S.; Dorasamy N. (Eurasia: Economics & Business, 2023)
This paper examined the import demand function for two panels, namely, BRICS and G7 countries, from 1992 to 2021. The study used panel time series data from the World Development Index (WDI). Choi test (Choi, 2006), Im, Peasaran, and Shin test (2003 unit root test) were used to test for stationarity. The tests indicated that variables became stationary at the first difference, I (0) and I (1). The Pedroni Cointegration Test exhibited a long-run relationship in G7 countries among the variables in question. However, for BRICS countries, the test indicated no long-run relationship between the variables in question. The dynamic ordinary least squares technique assessed the short- and long-run results. The results showed that real GDP influences import demand for both BRICS and G7 countries. Similarly, the real effective exchange rate antagonistically influences import demand capacity for G7 and BRICS countries. Pairwise Granger causality exhibited that there is bidirectional causality between real income (a real GDP proxy) and import demand in both trading blocs (BRICS and G7 countries). Even more along these lines, unidirectional causality runs from import price to import demand; however, in G7 countries, there is bidirectional causality between import price and import demand. Consequently, the policymakers for BRICS and G7 countries should monitor the movement of the authentic trading scale, real GDP, local prices, and import prices to stay aware of solidarity not yet settled in trade.